KAJIAN KARAKTER AKUNTANSI SYARIâAH: DULU, KINI, DAN ESOK - Prasetyo, Whedy (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2010)
Syariâah accounting based syariâah paradigm is Al-Qurâan, Hadis and Fiqh (Qias, Ijtihad, Ijma) to become obedient, right, dan responsibility to tauhid al-ibadah purpose for three relationship dimention, that is; (1) find willing of Allah SWT as main purpose to appoint social-economic fair, (2) benefit realization for society, to gives a obligation for societys, and (3) personal desire, to gives the require self. Syariâah accounting development based two factors, First, apart of society concept to hold on syariat accomplishment according to general, and especially how the society to hold commitment for accounting implementation based on syariâah. In the second, the syariâah accounting practices not only just to philosophy level, but from beliefing of philosophy that discanded in the real practices. To become development next periode of syariâah accounting: (1) growth open minded reflection, (2) adjust the true perspektif about Islam, (3) growth the institutions of syariâah implementation, (4) gives caring to development of syariâah implementation, and (5) doing together trade with entiring of component. Keywords: Syariâah accounting, and syariâah paradigm